Pengembangan Aplikasi Web Penerimaan Beasiswa Menggunakan Model Waterfall - Mulyati, Sri; Syawali, Fabian; Slameto, Ilham Ngudi; Nugraha, Rifaldi Setia; Ratama, Niki (Program Studi Teknik Informatika Universitas Pamulang, 2022)
In this modern era education is very important, but we can find some students or students who cannot continue their education due to costs, the provision of educational assistance from the government can help underprivileged students or students, the information we get, we create a web-based application that help students or students to get scholarships, from applications that we develop or make using several methods, sorting data, how to manage this web-based application from applicants, will be re-managed and put into a list, this based application can be a place of submission by web-based, submission of scholarship data can be viewed by registrants on the web can view the schedule or scholarship data, the data source that displays this web-based application is made to make it easier for students or students who want to study, but this web-based application is made only as a bridge or assistance to eat go to schools or universities that are worthy of education, the creation of web-based applications is intentionally not made with some complicated tools, only focused on applying for scholarships that may be able to help students or students who want further education.